The increasing necessity for the inclusion of process and production methods (PPMs) into the current GATT regime as a safeguard/tool for environmental sustainability - Matawu, Daniel Tawanda (Department of Commercial Law, 2015)
The aim of this thesis is to advocate for the inclusion of PPMs into the current GATT regime for the attainment of environmental sustainability. The issue of PPMs in international trade has been problematic for environmentalists since the first Tuna-Dolphin panel held that distinctions between products based on their production methods were not permissible under GATT. In the first part the thesis assessed and confirms that trade and the environment are two intertwined elements. The thesis then focused on the current legal framework within which environmental interests are said to be appreciated. It is shown that this framework is not efficient in protecting the environment. The thesis then identifies the issue of PPMs and their position in relation to the GATT. This analysis entailed a detailed study of article I, III and XX. It is shown that in many disputes involving PPMs, in most instances PPMs are easily found to be in contravention of the most-favoured nation principle (article I) and the national treatment principle(article III). An evaluation of article III also shows that the like products tests has made it challenging for PPMs to be acceptable in GATT. As for article XX most PPMs readily qualify under (b) and (g) but fail to meet the chapeau's steep requirements. In conclusion focus was on the PPMs debate vis-Ã -vis the views of developing and developed nations. By showing the rate of environmental degradation in the SADC region as examples, the thesis argues that PPMs offer developing countries a solution for environmental sustainability.